(untitled) (Medical Forum Monthly, 2024)
Aims and objectives-To study the frequency of occurrence of thyroglossal duct cyst in comparison to other midline neck swellings. Study Design: It is a prospective descriptive study. Place and Duration of Study: It is conducted in SUI in Allied hospital Faisalabad from March 2006 to March 2008. Materials and Methods: In this study 35 patients were studied. They were admitted through outdoor to surgical unit I with midline neck swellings. Patients of both sexes from 5 to 45 years old were examined. Their detailed history and physical examination were carried out. It was determined on physical examination that the midline swellings were solid or cystic, tender or non tender and moved with swallowing and tongue protrusion or not. Inclusion criteria: All patients with central midline swellings of the neck. Exclusion criteria: Patients with lateral neck swellings were excluded from this study. Results: In our study of 35 patients of midline neck swellings, 21 were males and 14 were females. Out of 35 patients 20 patients(57.14%) were having acute or chronic lymphadenitis, One out of 35 patients had Hodgkin’s lymphoma(2.85%),3 patients (8.5%) had thyroglossal cysts,8 patients(22.85%)had solitary thyroid nodule of isthmus,2 patients(5.7%)were suffering from dermoid cyst while 1 patient(2.8%) had plunging ranula. Out of 3 patients of thyroglossal cysts 2(5.71%) were males and 1(2.85%) was female. The age range was between 5 to 45 years. Conclusion: Lymph node enlargement are among the most common causes of midline neck swellings. Thyroglossal cysts are also found among the midline neck swellings but not as frequently as solitary thyroid nodules of the isthmus. Dermoid cysts and plunging ranulas are quite rare causes of midline neck swellings.